Heavy metal and metalloid toxicity in horticultural plants: Tolerance mechanism and remediation strategies. (September 2022) - Noor, Iqra; Sohail, Hamza; Sun, Jingxian; Nawaz, Muhammad Azher; Li, Guohuai; Hasanuzzaman, Mirza; Liu, Junwei
Abstract: Heavy metal/metalloids (HMs) are among the primary soil pollutants that limit crop production worldwide. Plants grown in HM contaminated soils exhibit reduced growth and development, resulting in a decrease in crop production. The exposure to HMs induces plant oxidative stress due to the formation of free radicals, which alter plant morphophysiological and biochemical mechanisms at cellular and tissue levels. When exposed to HM toxicity, plants evolve sophisticated physiological and cellular defense strategies, such as sequestration and transportation of metals, to ensure their survival. Plants also have developed efficient strategies by activating signaling pathways, which induce the expression of HM transporters. Plants either avoid the uptake of HMs from the soil or activate the detoxifying mechanism to tolerate HM stress, which involves the production of antioxidants (enzymatic and non-enzymatic) for the scavenging of reactive oxygen species. The metal-binding proteins including phytochelatins and metallothioneins also participate in metal detoxification. Furthermore, phytohormones and their signaling pathways also help to regulate cellular activities to counteract HM stress. The excessive levels of HMs in the soil can contribute to plant morpho-physiological, biochemical, and molecular alterations, which have a detrimental effect on the quality and productivity of crops. To maintain the commercial value of fruits and vegetables, various measures should be considered to remove HMs from the metal-polluted soils. Bioremediation is a promising approach that involves the use of tolerant microorganisms and plants to manage HMs pollution. The understanding of HM toxicity, signaling pathways, and tolerance mechanisms will facilitate the development of new crop varieties that help in improving phytoremediation. Graphical abstract: Image 1 Highlights: HM stress is a global issue that deteriorates the production and quality of horticultural crops. Free radicals induced by HM cause oxidative stress and alter cellular activities in plants. Plants respond to stress by activating signaling pathways that trigger HM-responsive transporters. Plants have evolved a variety of HM-stress tolerance strategies. Remediation is a potential method for the elimination of HM contamination.